Lessons for leaders: positive organization studies meets Niccolò Machiavelli - Cunha, M. P. (2017)
Machiavelli should be a central and canonical text for management education, even in the age of positive organizational literatures. We do so by considering the case of the virtuous leader. Our proposition is simple: virtuous leaders live and act, like anybody else, in the power circuits that are constitutive of reality. Therefore, they participate in power dynamics that sometimes make them face the need to decide in ways that do not correspond to normative positive precepts. Machiavelli shows that even the virtuous leaders must do what needs to be done, while trying to preserve one’s values and move in the direction of noble, high purpose goals.